3x + 12 can also be written as 3(x + 4)
Since both terms here are divisble by 3 then divide by 3 and factor our a 3...9/3x + 12/33(3x+4)
15x^2+3x-12 3(5x^2+x-4)=Answer
3x^4 - 12 = 3(x^4 - 4) = 3(x² + 2)(x² - 2)
(3x - 2)(2x + 6) or 2(3x - 2)(x + 3)
3x + 12 can also be written as 3(x + 4)
Since both terms here are divisble by 3 then divide by 3 and factor our a 3...9/3x + 12/33(3x+4)
15x^2+3x-12 3(5x^2+x-4)=Answer
(3x + 4)(5x + 3)
3
3x^4 - 12 = 3(x^4 - 4) = 3(x² + 2)(x² - 2)
(3x - 2)(2x + 6) or 2(3x - 2)(x + 3)
(3x - 4)(4x - 3)
(3x+12)(5x+2)
Since 3x is a factor of 3x^2, it is automatically the GCF.
Your factors must begin 3x and x to give 3x2. The factors of 12 are 1/12, 2/6 and 3/4. Which pair, together with 3x and x, can add to -5? 3 and 4 seem to fit the bill: (3x + 4)(x - 3)
factor out a 3x 3x(x-3)=3x2-9x